Supply Chain Performance Measurement Models: A Comparative Study - Saleheen, Ferdoush; Habib, Md Mamun (International Journal of Supply Chain Management, 2022)
The study investigated supply chain performance measurement models based on the primary and the secondary data and the justification of this paper is to evaluate the literature on performance measurement of the supply chain to capture current practices, distinguish gaps and advocate future research prospects used through a comparative study of different supply chain models. As of today, the measurement of supply chain performance is dependent on the Balanced Scorecard (BSC) and the Supply Chain Operations Reference (SCOR) model which requires the adaptation of a holistic approach such as the application of sustainability, and resilient supply chain considering the constant change of the business dynamics. As a result, many manufacturing companies failed to attain a precise performance measurement evaluation due to a lack of an Integrated Supply Chain Performance Measurement (ISCPM) model and knowledge in the manufacturing industry. This study illustrates the Integrated Supply Chain Performance Measurement (ISCPM) model and makes a comprehensive comparison with the BSC and the SCOR model. ISCPM model has been developed through the supply chain performance attributes and performance measurement index in the outlook of input-process-output considering the BSC and the SCOR model at three decisions levels with an application of quantitative techniques to bring synergic effect to all stakeholder issues and incorporates ten supply chain performance measurement attributes and 36 performance measurement indexes as supplier relationship management (SRM), internal supply chain management (ISCM), and customer relationship management (CRM).